Blast associated genotyping-by-sequencing markers for marker-assisted selection and genomic profiles of 4,143 wheat breeding lines for the 2NS translocation. - CGIAR Research Program on Wheat (2020)
Breeders develop blast resistant wheat varieties more efficiently through better understanding of the shared genetic basis of blast resistance across different geographical regions and genomic characterization of breeding lines for the 2NS translocation.